Learning Environments Designed According to Learning Styles and Its Effects on Mathematics Achievement - Özerem, Ayşen; Akkoyunlu, Buket (Eurasian journal of educational research, 2015)
Problem Statement: While designing a learning environment it is vital to think about learner characteristics (learning styles, approaches, motivation, interests… etc.) in order to promote effective learning. The learning environment and learning process should be designed not to enable students to learn in the same manner and at the same level, but rather designed by giving thought to students' existing learning styles. Purpose of the Study: The aim of this study is to examine primary students' and inspectors' opinions on different learning environments designed according to students' learning styles and its effects on students' achievement. Method: Fifty-five seventh grade students and seven inspectors constituted the research sample. The data were collected through an open-ended questionnaire; a mathematics achievement test and the Pat Wyman Personal Learning Style Inventory were used as data collection tools in the research. Since the group consisted of less than 30 participants, the Wilcoxon Signed Rank Test for Paired Samples was used. Findings and Results: The difference of pre-post test results of visual auditory learners, auditory-kinesthetic learners, and visual-auditory learners are statistically significant. When the ranked average of different grades and their sums are considered, the observed difference is in positive ranking, meaning it is in favor of post-test results. According to these results, different learning environments designed for visual-auditory-kinesthetic learners have a positive effect on student grades. The majority of the students stated that the aforementioned activities used in the mathematics lesson could also be used in other school subjects. Conclusions and Recommendations: Student responses emphasized that learning environments should be designed according to student learning styles. Inspectors underlined that learning styles designed according to students' individual learning styles may increase student success. In addition, inspectors thought that some of the advantages of designing learning environments according to students' learning styles included an opportunity to learn fairly, an increase in student motivation towards the lesson, and enabling students to learn at their own pace. In the upcoming studies, student behaviors and motivations towards environments designed according to students' learning styles will be analyzed.